DETERMINING THE IN-SERVICE TRAINING NEEDS OF GUIDANCE TEACHERS - (:unkn) unknown (ISOSS PUBL, 2014)
The purpose of this study is to determine the in-service training need of the guidance teachers. The research was designed as a qualitative case study. The participants were 27 guidance teachers working in 11 district state schools in Istanbul during 2013-2014 school year. The data were obtained using a semi structured interview form. The interviews with the guidance teachers were recorded in the audio format and then transcribed and coded into themes, which were tabled with percentage and frequencies. As a result of the study, it was understood that guidance teachers felt themselves inadequate mostly in terms of guiding students in need of special education and inclusion, and in terms of counselling techniques and vocational guidance. It was also found that the participating guidance teachers would like to have in-service training about intervention to the traumatic cases, special education, solution-focused therapy with drama and counselling techniques. It was also understood that guidance teachers believe their colleagues need to have in-service training mostly about counselling techniques, solution-focused therapy, family counselling and communication skills.
Keywords: SCIENCE TEACHERS